Confinement‐Driven Enantioselectivity in 3D Porous Chiral Covalent Organic Frameworks. Issue 11 (28th January 2021) - Hou, Bang; Yang, Shi; Yang, Kuiwei; Han, Xing; Tang, Xianhui; Liu, Yan; Jiang, Jianwen; Cui, Yong
Abstract: 3D covalent organic frameworks (COFs) with well‐defined porous channels are shown to be capable of inducing chiral molecular catalysts from non‐enantioselective to highly enantioselective in catalyzing organic transformations. By condensations of a tetrahedral tetraamine and two linear dialdehydes derived from enantiopure 1, 1′‐binaphthol (BINOL), two chiral 3D COFs with a 9‐fold or 11‐fold interpenetrated diamondoid framework are prepared. Enhanced Brønsted acidity was observed for the chiral BINOL units that are uniformly distributed within the tubular channels compared to the non‐immobilized acids. This facilitates the Brønsted acid catalysis of cyclocondensation of aldehydes and anthranilamides to produce 2, 3‐dihydroquinazolinones. DFT calculations show the COF catalyst provides preferential secondary interactions between the substrate and framework to induce enantioselectivities that are not achievable in homogeneous systems. Abstract : Chiral 3D COFs with interpenetrated open frameworks were synthesized from tetrahedral tetraamine and enantiopure BINOL dialdehydes. The resulting 3D COF was capable of inducing chiral molecular catalysts from non‐enantioselective to highly enantioselective under confinement effect in catalyzing important organic transformation with high catalytic activity and good recyclability.